Two Types of Tradition in the “Khaan Siir Bodon” Chapter of the Jangar Epic - Tudev, Bayasgalan (Studia Folclorica, 2025)
This article presents a comparative study of four versions of the Jangar epic chapter “Khaan Siir Bodong” which has been transmitted orally in Mongolia and Xinjiang. The study argues that these versions can be classified into two types traditions: the school of the Jangar performer Shishneen Buural of Khovogsair and the school of the Jangar performer Pürev Taij of Bortala. Furthermore, the article identifies changes in the plot as reflected in the versions recited by the Jangar performers M. Pürevjal, B. Möntgör, P. Rampil, and T. Nyam, who learned and transmitted this chapter from Sh. Buural and Pürev. This chapter is believed to have originally emerged with the theme of heroic marriage. While traveling to marry the girl to whom he had been betrothed since childhood, Khaan Siir is deceived by a treacherous warrior named Orno-Ulaadai and is killed while asleep. Orno-Ulaadai then disguises himself as Khaan Siir and goes to claim the bride. At this point, Khongor arrives, exposes and captures the villain, restores Khaan Siir to life, and unites him with his bride forming the core narrative of the episode. Although the chapter depicts the marriage of Khaan Siir, it may essentially be regarded as a chapter devoted to the heroic merits of Khongor. More specifically, the article suggests that this chapter emerged during the period when Khongor’s image had evolved into that of the founder, savior, and protector of the realm of Bumba, and that it was newly formed in connection with this development of Khongor’s character in the 17th–18th centuries. “Жангар” туулийн Хаан Сийр бодонгийн бүлгийн хоёр зүйлийн уламжлал Хураангуй: Энэ өгүүлэлд Монгол, Шинжаанд амаар дэлгэрсэн “Жангар” туулийн Хаан Сийр бодонгийн бүлгийн дөрвөн хувилбарыг харьцуулж судлаад, эдгээр нь Ховогсайрын жангарч Шишнээн Бууралын дэг сургууль, Борталын Жин шианы жангарч Пүрэв тайжийн дэг сургууль гэсэн хоёр төрөлд хуваагдаж байна гэж үзжээ. Улмаар Ш.Буурал, Пүрэв нараас тус бүлгийг сурч, уламжлан дамжуулсан М.Пүрэвжал, Б.Мөнтгөр, П.Рампил, Т.Ням нарын жангарчдын хэлсэн хувилбаруудад үйл явдлын талаар ямар өөрчлөлт гарсныг тодруулсан байна. Тус бүлэг нь анх баатарлаг гэрлэлтийн сэдэвтэйгээр үүсжээ. Хаан Сийр хөвгүүн насны багад нь өндгөн сүй тавьсан бүсгүйгээ авахаар явж байх замдаа Улаадай гэгч хорон санаат баатарт итгэж гэнэдээд, унтаж байхдаа хөнөөгддөг. Улаадай, Хаан Сийрийн дүрд хувираад, сүйт бүсгүйг нь авах гээд очсон үед Хонгор ирж хортныг илчлэн, барьж аваад, Хаан Сийрийг амь оруулж, сүйт бүсгүйтэй нь гэрлүүлсэн тухай ерөнхий өгүүлэгдэхүүнтэйгээр үүссэн байна. Энэ бүлэгт Хаан Сийр хөвгүүний гэрлэлтийг үзүүлсэн боловч, Хонгор баатрын алдар гавьяаны тухай бүлэг гэж болно. Тодруулбал, энэ бүлэг Хонгорын дүр Бумбын орныг төвхнүүлэгч, аврагч, хамгаалагч хэв шинжтэй болсон цаг үед буюу Хонгорын дүрийн хөгжилтэй уялдаж XVII-XVIII зуунд шинээр үүссэн гэж үзжээ. Түлхүүр үг: дэг сургууль, Мишигдорж ван, Орно-Улаадай, урын сан